2006
DOI: 10.1098/rstb.2006.1882
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular control of developmental and regenerative axon growth

Abstract: Axon growth is a highly regulated process that requires stimulating signals from extracellular factors. The extracellular signals are then transduced to regulate coordinately gene expression and local axon assembly. Growth factors, especially neurotrophins that act via receptor tyrosine kinases, have been heavily studied as extracellular factors that stimulate axon growth. Downstream of receptor tyrosine kinases, recent studies have suggested that phosphatidylinositol-3 kinase (PI3K) regulates local assembly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(141 citation statements)
references
References 145 publications
2
139
0
Order By: Relevance
“…In the developing nervous system, GSK3 regulates the activity of several microtubule associated proteins (MAPs) 4,13,[21][22][23]38,39 and thereby controls directed growth cone advancement and guidance. One of these proteins is MAP1B, which is required for axon growth 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In the developing nervous system, GSK3 regulates the activity of several microtubule associated proteins (MAPs) 4,13,[21][22][23]38,39 and thereby controls directed growth cone advancement and guidance. One of these proteins is MAP1B, which is required for axon growth 40 .…”
Section: Discussionmentioning
confidence: 99%
“…GSK-3 has multiple substrates that have the potential to regulate tubulin polymerization and microtubule stability. These include the microtubule plus-end binding proteins APC and CLASP2, CRMP-2, which is localized to axon tips and may play a role in cargo delivery and tubulin polymerization, and the microtubule associated proteins MAP1B and tau (reviewed in Zhou and Snider 2006). Details of how these proteins function and how they are regulated by GSK-3 phosphorylation remain obscure.…”
Section: Gsk-3 and Axon Elongationmentioning
confidence: 99%
“…Thus, many studies with the major pharmacological inhibitors PD98059 and U0126 show striking inhibition of axon growth induced by neurotrophins and other factors acting via receptor tyrosine kinases (see Zhou and Snider 2006, for a review). Further, both loss and gain of function studies in vitro suggested strong axon growth promoting functions for Ras, Raf, and ERK/MAPK (Markus et al 2002).…”
Section: Initiating and Growing An Axonmentioning
confidence: 99%
“…the brain and spinal cord) is a particularly challenging tissue system in this regard, due to the complex cellular dynamics and intricate (cardinal) pathophysiological events displayed after neurological injury [13]. For example, following SCI in vivo: astrocytes upregulate expression of the astrocyte-specific marker glial fibrillary acidic protein (GFAP), within and adjacent to lesions, to form a scar that constitutes a critical barrier to axonal regeneration [14]; microglia (the immune-competent cells of the CNS) infiltrate into lesion sites and are responsible for the breakdown and phagocytosis of cellular debris and toxic substances following injury [15,16]; and limited, spontaneous sprouting of nerve fibers occurs from lesion margins, with the extent of regeneration declining with age [17].…”
Section: Introductionmentioning
confidence: 99%